Quantitative analysis of Brazilian football players' organisation on the pitch - Arruda Moura, F.; Barreto Martins, L. E.; de Oliveira Anido, R.; Leite de Barros, R. M.; Cunha, S. A. (Sports Biomechanics, 2012)
The purpose of this study was to characterise Brazilian teams' coverage area and spread on the pitch while attacking and defending and to analyse the teams' organisation in tackle and shot on goal situations. We obtained the trajectories of 223 players in eight games with a tracking method. Team area was defined as the area of the convex hull formed by players' positions. Team spread was defined as the Frobenius norm of the distance-between-player matrix. We calculated teams' area and spread over time and in situations of shots on goal (n = 233) and tackles (n = 1,897). While the players attacked, spread and area (median ± confidence interval) ranged from 322.9 ± 0.8 to 387.8 ± 1.0 m and from 905.4 ± 4.4 to 1,407.6 ± 5.5 m2, respectively. On defence, the values were smaller (p < 0.05) and ranged from 283.4 ± 0.9 to 325.8 ± 0.9 m and from 773.8 ± 4.6 to 1,158.4 ± 5.5 m2 for the spread and the area. In defending circumstances, the teams presented a greater area and spread when they suffered shots on goal than when the teams performed tackles. In attacking situations, the teams presented a greater area and spread when they suffered tackles than when they performed shots on goal. The results allowed showing the attacking-defending interaction between Brazilian teams.